Postembedding Decalcification of Mineralized Tissue Sections Preserves the Integrity of Implanted Biomaterials and Minimizes Number of Experimental Animals. (23rd March 2017) - El Khassawna, Thaqif; Daghma, Diaa Eldin S.; Stoetzel, Sabine; Ray, Seemun; Kern, Stefanie; Malhan, Deeksha; Alt, Volker; Thormann, Ulrich; Henß, Anja; Rohnke, Marcus; Stengel, Annette; Hassan, Fathi; et al.
Abstract : Bone histology of decalcified or undecalcified samples depends on the investigation. However, in research each method provides different information to answer the scientific question. Decalcification is the first step after sample fixation and governs what analysis is later feasible on the sections. Besides, decalcification is favored for immunostaining and in situ hybridization. Otherwise, sample decalcification can be damaging to bone biomaterials implants that contains calcium or strontium. On the other hand, after decalcification mineralization cannot be assessed using histology or imaging mass spectrometry. The current study provides a solution to the hardship caused by material presence within the bone tissue. The protocol presents a possibility of gaining sequential and alternating decalcified and undecalcified sections from the same bone sample. In this manner, investigations using histology, protein signaling, in situ hybridization, and mass spectrometry on the same sample can better answer the intended research question. Indeed, decalcification of sections and grindings resulted in well-preserved sample and biomaterials integrity. Immunostaining was comparable to that of classically decalcified samples. The study offers a novel approach that incites correlative analysis on the same sample and reduces the number of processed samples whether clinical biopsies or experimental animals.